2014
DOI: 10.1111/aec.12115
|View full text |Cite
|
Sign up to set email alerts
|

Buffering against food availability? The physical environment has little influence on breeding performance of fairy prions (Pachyptila turtur)

Abstract: The breeding performance of seabirds is constrained by the availability of marine-based prey, which may be influenced by competition with other seabirds, and environmental conditions. Fairy prion (Pachyptila turtur) populations have declined substantially in New Zealand since the introduction of mammalian predators; remaining small populations provide an opportunity to examine the effect of environmental factors on reproductive success in the absence of competition. Using 11 years of nest monitoring data and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…In southeastern Australia and New Zealand, the locally abundant coastal krill Nyctiphanes australis [ 82 ] is a key food source for CDP [ 34 ] (C. M. Miskelly 2019, personal observation). However, this euphausiid undergoes extreme inter-annual variations in biomass and distribution, considerably affecting the reproductive success of various fish [ 82 ] and seabird species [ 84 , 85 ]. Populations spending a long period near the colony before the reproductive season are more likely to follow local environmental cues to adapt their phenology [ 83 ], which may explain the significant delay in the breeding period observed between the years in the present study at Kanowna Island [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…In southeastern Australia and New Zealand, the locally abundant coastal krill Nyctiphanes australis [ 82 ] is a key food source for CDP [ 34 ] (C. M. Miskelly 2019, personal observation). However, this euphausiid undergoes extreme inter-annual variations in biomass and distribution, considerably affecting the reproductive success of various fish [ 82 ] and seabird species [ 84 , 85 ]. Populations spending a long period near the colony before the reproductive season are more likely to follow local environmental cues to adapt their phenology [ 83 ], which may explain the significant delay in the breeding period observed between the years in the present study at Kanowna Island [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a key zooplankton species (Ritz & Hosie 1982), variability in abundance of coastal krill has been observed to influence the foraging behaviour and demographic parameters of various marine predators (Mills et al 2008, Manno et al 2014. For example, in New Zealand, delayed breeding period, longer foraging trips and low breeding success of the zooplanktivorous red-billed gull (Larus novaehollandiae scopulinus) were linked to the absence of coastal krill in years of positive sea temperature anomaly (Mills et al 2008).…”
Section: Inter-annual Variation In Breeding Success Foraging Behaviou...mentioning
confidence: 99%
“…However, in contrast with the sympatric common diving petrels, fairy prions appeared to buffer the variations in environmental conditions better, owing to their higher flight capacity and the production of stomach oil [ 33 , 66 ]. Indeed, despite being smaller than common diving petrels, the lower wing load of fairy prions enables them to reach more distant foraging areas [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly concerning as the frequency and intensity of such extreme events are predicted to increase in the near future [ 28 ]. In addition, although recent studies showed that fairy prions are able to maintain a relatively good breeding success even during poor years [ 33 , 66 ], the long-term consequences of marine heatwaves on juveniles' and adults’ survival remain totally unknown.…”
Section: Discussionmentioning
confidence: 99%